2017
DOI: 10.1016/j.jaci.2016.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Alanine-scanning mutagenesis of human signal transducer and activator of transcription 1 to estimate loss- or gain-of-function variants

Abstract: Background Germline heterozygous mutations in human STAT1 can cause loss of function (LOF), as in patients with Mendelian susceptibility to mycobacterial diseases (MSMD), or gain of function (GOF), as in patients with chronic mucocutaneous candidiasis (CMC). LOF and GOF mutations are equally rare and can affect the same domains of STAT1, especially the coiled-coil and DNA-binding domains (CCD/DBD). Moreover, 6% of CMC patients with a GOF STAT1 mutation develop mycobacterial disease, obscuring the functional si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 63 publications
2
73
0
Order By: Relevance
“…Since the discovery of its first genetic etiology in 1996, MSMD has been reported and a causal genetic lesion described in 501 individuals from 356 kindreds originating from 57 countries on five continents (Figure a). Over this period, the genetic dissection of MSMD in these patients has revealed this condition to be caused by inborn errors of interferon (IFN)‐γ immunity . These findings confirm that IFN‐γ, first described in 1965 as an antiviral IFN, is actually the macrophage‐activating factor, as shown in 1983 .…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Since the discovery of its first genetic etiology in 1996, MSMD has been reported and a causal genetic lesion described in 501 individuals from 356 kindreds originating from 57 countries on five continents (Figure a). Over this period, the genetic dissection of MSMD in these patients has revealed this condition to be caused by inborn errors of interferon (IFN)‐γ immunity . These findings confirm that IFN‐γ, first described in 1965 as an antiviral IFN, is actually the macrophage‐activating factor, as shown in 1983 .…”
Section: Introductionsupporting
confidence: 61%
“…Since the last comprehensive review on MSMD in 2014, three new genetic disorders have been reported, caused by mutations of TYK2 and SPPL2A, (two novel genetic etiologies) and IFNGR2 (a novel allelic form). Moreover, new mutations associated with the other 18 disorders have also been reported . We also discuss here two recently reported syndromic forms of MSMD: AR RORγ/RORγT and Janus kinase (JAK)1 deficiencies .…”
Section: Introductionmentioning
confidence: 80%
“…BCG disease has been reported in CGD patients, but cases of M. avium complex infection have rarely been reported in this population. Moreover, these 2 mycobacterial infections are probably not related to p40 phox deficiency in P19, because this patient also carries a dominant-negative STAT1 mutation responsible for MSMD (47 The production of intracellular ROS by neutrophils, monocytes, and NB4 cells was analyzed with DHR (Thermo Fisher Scientific), as previously described (66). We added 0.5 μM DHR in DMSO to 2.5 × 10 6 neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…This same patient subsequently suffered from meningitis caused by Mycobacterium avium. Interestingly, this patient was also heterozygous for a dominant-negative LOF mutation of STAT1, which is responsible for MSMD (47). Four asymptomatic children, aged 1, 3, 8, and 10 years at diagnosis of p40 phox deficiency, were healthy controls, and unlike MDDCs from classic CGD patients ( Figure 5B).…”
Section: Peripheral But Not Invasive Infections In Patients With P40mentioning
confidence: 99%
“…Clinical presentation is in most of the cases multifocal MOM caused by environmental mycobacteria (EM), mainly M. avium or BCG. MOM is a frequent manifestation in AD IFN- γ R1 or AD STAT1-deficient patients, all but one as disseminated osteomyelitis [34-38]. Additionally, patients with autosomal recessive (AR) IFN- γ R1 deficiency have been described with MOM as part of disseminated mycobacterial disease.…”
Section: Discussionmentioning
confidence: 99%